Building a 3D Petrophysical Model for Mishrif Formation in Nasiriyah Oil Field, Southern Iraq - Abdullah, Murtadha Doghiam; Nasser, Medhat E.; AL-Yasseri, Abdullah A. (Iraqi Journal of Science, 2019)
A 3D geological model for Mishrif Reservoir in Nasiriyah oil field had been invented "designed" "built". Twenty Five wells namely have been selected lying in Nasiriyah Governorate in order to build Structural and petrophysical (porosity and water saturation) models represented by a 3D static geological model in three directions .Structural model showed that Nasiriyah oil field represents anticlinal fold its length about 30 km and the width about 10 km, its axis extends toward NW–SE with structural closure about 65 km . After making zones for Mishrif reservoir, which was divided into 5 zones i.e. (MA zone, UmB 1zone,MmB1 zone ,L.mB1 zone and mB2zone) .Layers were built for each zone depending on petrophysical properties. MA(1 layer) ,UmB1(6 layer) ,MmB1 (8 layer) LmB1(6 layer) and mB2(5 layer) Petrophysical models (porosity and water saturation) had been constructed for each zone of Mishrif reservoir using random function simulation algorithm. According to data analyses and the results from modelling, the MB1zone is a good reservoir unit regarding its good petrophysical properties (high porosity and low water saturation) with high presence of oil in economic quantities.